Evaluation of Relationships between Menopause Onset Age and Bone Mineral Density and Muscle Strength in Women from South-Western Poland - Fugiel, Jarosław (Biomed Res Int, 2020)
INTRODUCTION: The onset of the menopause entails numerous changes, both physical and mental, in the functioning of the bodies of women. Moreover, the early menopause increases the risk of occurrence of many civilization-related diseases. Major factors contributing to health deficits include lowered bone mineral density and sarcopenia, which can result in serious functional limitations and the acceleration of ageing processes in the body. The aim of this study was to determine how the menopause onset age is linked with bone mineral density and the strength of selected muscles of the limbs and the trunk. Material and Methods. 756 women aged 50-80 years were subjected to tests. The subjects were divided into three groups: (I) from 50 to 59 years, (II) from 60 to 69 years, and (III) from 70 to 79 years. Each of the women specified the age when her final menstrual period occurred. On this basis, groups of women with (1) the early menopause—before the 50th year of life—and (2) with the late menopause—after the 50th year of life—were distinguished. Bone mineral density (BMD), dominant hand grip strength, knee extensor and flexor strength, and functional upper and lower body muscle strength were determined in each of the women. RESULTS: The test results indicate differences in levels of muscle strength and BMD between the 50-year-old early- and late-menopausal women. The late-menopausal women score better motor ability test results and higher BMD values. The differences decrease in the groups of 60-year-old women, whereas the 70-year-old early- and late-menopausal women score similar results. CONCLUSIONS: A higher percentage of women with a lowered bone mass and a lower strength level was found in the group of early-menopausal subjects. The rate of decline in hand grip strength, the functional efficiency of the upper and lower limbs, and BMD is faster in the late-menopausal women, whereby the two groups of 70-year-old women score similar test results.